Factores de riesgo y manejo terapéutico de diabetes mellitus tipo 2, en el Hospital Regional Isidro Ayora - Benavides Arévalo, Tanya Elizabeth (2015)
Diabetes Mellitus Type 2 is one of the leading causes of death in our country, that is why it has been decided to know what the risk factors and therapeutic management are in patients treated at the General Hospital Isidro Ayora in Loja city. This work is descriptive, retrospective and cross-cutting, collecting data through clinical records of 153 patients with Type 2 Diabetes Mellitus attended for the first time in the outpatient area, Endocrinology Service in the months from January to June 2014, Which of the 52.6% are female, and 32.7% are aged between 50-59 years, the main risk factors are overweight-obesity in 68.6%, presence of triglycerides in 41.1% and 40.5% decreased High Density Lipoprotein; and their initial treatment is 66.7% with oral antidiabetic metformin either alone or in combination with glimepiride or glibenclamide and 33.3% received insulin with NPH and regular insulin in an interleaved or mixed as the 70/30. Thus determined that there is a predominance of the disease in women aged 50-59 years with the presence of predisposing risk factors for the development and subsequent complications of Type 2 Diabetes Mellitus and proper treatment in the study mostly with oral agents. Keywords: Type 2 Diabetes Mellitus, Risk Factors, Therapeutic management